Integrative network analysis of signaling in human CD34+ hematopoietic progenitor cells by global phosphoproteomic profiling using TiO2 enrichment combined with 2D LC‐MS/MS and pathway mapping. Issue 8 (6th March 2013) - Guo, Hongbo; Isserlin, Ruth; Chen, Xiaoji; Wang, Weijia; Phanse, Sadhna; Zandstra, Peter W.; Paddison, Patrick J.; Emili, Andrew; Figeys, Daniel
<x xml:space="preserve">Abstract</x> Protein kinase signaling regulates human hematopoietic stem/progenitor cell (HSPC) fate, yet little is known about critical pathway substrates. To address this, we have developed and applied a large‐scale, empirically optimized phosphopeptide affinity enrichment strategy with high‐throughput 2D LC‐MS/MS screening to evaluate the phosphoproteome of an isolated human CD34+ HSPC population. We first used hydrophilic interaction chromatography as a first dimension separation to separate and simplify protein digest mixtures into discrete fractions. Phosphopeptides were then enriched off‐line using TiO2‐coated magnetic beads and subsequently detected online by C18 RP nanoflow HPLC using data‐dependent MS/MS high‐energy collision‐activated dissociation fragmentation on a high‐performance Orbitrap hybrid tandem mass spectrometer. We identified 15 533 unique phosphopeptides in 3574 putative phosphoproteins. Systematic computational analysis revealed biological pathways and phosphopeptide motifs enriched in CD34+ HSPC that are markedly different from those observed in an analogous parallel analysis of isolated human T cells, pointing to the possible involvement of specific kinase‐substrate relationships within activated cascades driving hematopoietic renewal, commitment, and differentiation.